A rare case of extensive pemphigus vegetans - Ghanshyam K Verma; Gita R Tegta; Anuj Sharma; Mohitpreet Kaur; Sudarshan Sharma (Wolters Kluwer Medknow Publications, 2020)
Pemphigus vegetans is a rare variant of pemphigus vulgaris characterized by pustules and/or papillomatous vegetations, preferentially affecting intertriginous and periorificial areas. It has two subtypes: Hallopeau variant and Neumann variant. Cerebriform tongue, a morphology with typical pattern of sulci and gyri over dorsum of the tongue, is a well-known sign in pemphigus vegetans. We are presenting an unusual case of pemphigus vegetans with extensive involvement of mucosae, trunk, extremities including both extensors and flexural areas with verrucous paronychia and fissured tongue. During clinical exam we recognized multiple cutaneous vesicles, erosions and ulcers on mucosal sites. Clinical, histopathological, and direct and indirect immunofluorescence findings were compatible with pemphigus vegetans. Patient had completed her family so treated with intravenous dexamethasone-cyclophosphamide pulse (DCP) regimen with excellent response.